G448(P) Nosocomial neonatal listeria monocytogenes transmission: a report of two cases and a review of the literature. (27th April 2015) - Fullerton, L; Norrish, G; Wedderburn, C; Paget, S; Cane, C; Basu-Roy, R
Abstract : Introduction: Listeria monocytogenes is an uncommon but serious cause of neonatal sepsis. There is significant morbidity associated with neonatal listeriosis with reports of 23% having long term moderate to severe disability at 10 years. 1 We report the nosocomial transmission of L. monocytogenes IV4 47 from a premature baby with early onset sepsis to a term baby with late onset meningitis. A junior doctor's stethoscope was identified as the likely mode of transmission highlighting the importance of comprehensive infection control precautions. Methods: Clinical governance review led to a root cause analysis and the subsequent need for further evaluation. We searched the literature using terms 'nosocomial infection' and ' Listeria ', with filters of 'English language' and 'birth to one month' in order to review the published literature. A poster campaign was initiated following this incident reminding all paediatric doctors attending labour ward, resuscitation and post–natal ward to clean their stethoscopes after contact with each patient. Results: A PubMed search using the search teams 'nosocomial infection' and ' Listeria ', with filters of 'English language' and 'birth to one month' returned 28 results. There were 12 case reports of transmission in a shared hospital geographical location however this is the first report of nosocomial transmission of Listeria across different geographical locations within a hospital by an individual's stethoscope. Following the poster campaign there have been no further reports of any nosocomial infection. Conclusion: Despite many case reports of nosocomial Listeria transmission in neonates, this still occurs with potential significant morbidity and mortality. Transmission of infection can occur by a variety of ways, which include personnel and equipment. The stethoscope is a vital piece of equipment carried by all doctors. Yet stethoscopes are often not cleaned regularly in between patient contact and are not identified as possible infection sources. Infection transmission is easily preventable by simple measures, which current national guidelines do not highlight. A lack of formal teaching and of senior role models actively cleaning their stethoscopes can contribute to poor stethoscope hygiene, 2 both of which are easy to address. References: Okike IO, Lamont RF, Trafford Heath P. Do we really need to worry about Listeria in Newborn Infants? PIDJ 2013;32:405–406 Saunders C, Hryhorskyj L, Skinner J. Factors influencing stethoscope, Cleanliness among clinical medical students. J Hosp Infect. 2013;84:242–244